Oppositional Defiant Disorder, Conduct, and ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
The link between oppositional defiant disorder (ODD) and conduct disorder (CD) was evaluated in 140 children with attention-deficit hyperactivity disorder (ADHD) and 120 normal controls examined at baseline and 4 years later, in midadolescence, at the Pediatric Psychopharmacology Unit, Psychiatric Service, Massachusetts General Hospital, Boston, MA.